Cortisol and Obesity; a Stress Related Insight: Obesity and Cortisol - Thant, Zin; Nordin, Simbak; Atif, Amin Baig (2014)
Carusol has a well-known circadian array of secretion. The endogenous central pacemaker or the suprachiasmaticnucleus (SCN) of the body, controls the circadian rhythm of the HPA axis which affects adrenocortical activity by input to the hypothalamus. The role of hypothalamus has been well reported established in controling the hunger centers and so as if in controling the obesity. Two genes have been reported to control obesity of a person which includes Angiotensin Converting Enzyme (ACE) gene and PPAR gamma gene. Here we have discussed the correlation of all aspects of cortisol based stress with relation to induced obesity in such individuals.